Geography basics - Sumner, Ray (Magill's choice., 2004)
Geography Basics covers the most fundamental concepts of both physical and social geography. In order to further the geographic literacy of contemporary students, the articles in Geography Basics take an integrated approach to the field, emphasizing interconnections of every kind.